The development of interactive learning media in computer and basic networks subject on computer and netwroks engineering of SMKN 2 Lubuk Basung - Putra, Deni Ferdiansyah; Giatman, M (Universitas Negeri Padang, 2020)
The purpose of this research is to develop interactive learning media on computer and basic networks subject that are valid, practical and effective. This reasearch is used the Four-D design model that is applied to develop and test the validity, practicality and effectiveness of interactive learning media in computer and basic networkinglearning. The research is used the Four-D model include defining, designing, developing, and distributing. The results of the validity test on interactive learning media are valid. Based on teachers and students responses about instructional media shows the results of interactive learning media are very practical and learning outcomes from students indicate the learning media has been effectively used for computer and basic networkinglearning. The analysis resultshows that interactive learning media is better in improving student learning processes.